PENILAIAN DAN HASIL BELAJAR - Harefa, Amin Otoni (DIDAKTIK, 2009)
Abstrak: Evaluation that is including measurement, and assessment. Evaluation is process or activity to assess something. To be able to determine value of something thatÂ  assessing by measurement, and form of measurement is examination, and this examination in education recognized with term of test. Outcomes of learning is ability of student in fulfilling the step attainment of experience learn in one based competence. Learning outcomes of student based on indicator.Kata kunci: evaluation, learning outcomes.